Jawabanmu

2014-03-17T18:06:08+07:00
G.(9-y)6 = (2y+3)4
54-6y=8y+12
42=14y
y=3

h.
x+4=-3x+9
x+3x=9-4
4x=5
x=5/4
2014-03-17T18:15:31+07:00
A. 3t + 1 = 19              b. -3 = -8 + y                c. a/3 + 1 = 6
     3t = 18                          y = -3 + 8                    a/3 = 5
       t = 6                             y = 5                            a = 5 x 3 = 15

d. 9 - x          3x + 4
   ____  =    _____  ------->  45 - 5x = 12x + 16 --> 45 - 16 = 12x + 5x ----> 29 = 17x
        4                5                                                                                                      x = 17/29


f.3(x-4) + 5(4-x) = -4(x+2) , x ∈ R
   3x-12 + 20-5x = -4x -8
   -2x +8 = -4x - 8
   2x = -16
     x = -8
e.3(2x-5)  -3 = -2(-x+4)-(3x-1)
    6x -15 -3 = 2x -8 -3x + 1
    6x -18 = -x -7
     7x = 11
       x = 11/7

g. 9 - y      2y + 3
   ____ = _____ ----> 54 - 6y = 8y +12 --> 42 = 14y
       4             6                                                  y = 3


maaf h nya tidak, kalo ada yang salah maaf ya,
Smoga membantu :)